Atomic layer deposited-ZnO@3D-Ni-foam composite for Na-ion battery anode: A novel route for easy and efficient electrode preparation. Issue 1 (January 2019) - Sinha, Soumyadeep; Didwal, Pravin N.; Nandi, Dip K.; Cho, Jae Yu; Kim, Soo-Hyun; Park, Chan-Jin; Heo, Jaeyeong
Abstract: The sluggish kinetics of relatively larger Na-ion still limits the performance of sodium-ion batteries (SIBs) as compared to lithium-ion batteries (LIBs). In this context, a novel route is introduced by coating a thin films of ZnO on a porous 3D Ni-foam scaffold by atomic layer deposition (ALD) for the first time and is used as a superior anode for SIBs without any post-modifications. The scanning electron microscopy along with transmission electron microscopy studies reveal that highly crystalline ZnO can be deposited on such complex 3D Ni-foam with excellent uniformity and conformality. A stable reversible capacity of ~ 65.1 mAh g −1 up to 400 charge-discharge cycles and the excellent rate capability in a wide current density range (30–1000 mA g −1 ) establish the potential of this composite prepared by a direct and relatively easier method of electrode fabrication. The predominant alloying-dealloying based reactions for Zn-based anode material is also established in SIBs by the post-cycling X-ray photoelectron spectroscopic analyses. The post-cycling analysis of these anodes also reveals the robust structure with good adhesion of the ALD grown films on Ni-foam. In addition, similar study on 2D substrate elucidates the extra advantages of this current strategy. This model efficient route can easily be extended and adopted for any other materials to further enhance the performance of SIBs in future.